2015
DOI: 10.2337/dc14-1522
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Socioeconomic Status on Excess Mortality in a Population-Based Cohort of Subjects With Childhood-Onset Type 1 Diabetes

Abstract: OBJECTIVE The aim of this study was to analyze the possible impact of parental and individual socioeconomic status (SES) on all-cause mortality in a population-based cohort of patients with childhood-onset type 1 diabetes. RESEARCH DESIGN AND METHODS Subjects recorded in the Swedish Childhood Diabetes Registry (SCDR) from 1 January 1978 to 31 December 2008 were included (n = 14,647). The SCDR was linked to the Swedish Cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
4
11
0
Order By: Relevance
“…These results are in accordance with previous studies in which adults with Type 1 diabetes and low SES have been shown to have a higher risk of complications [19,20] and early death [21][22][23]. As a marker for SES, we used educational level and receipt of social support.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in accordance with previous studies in which adults with Type 1 diabetes and low SES have been shown to have a higher risk of complications [19,20] and early death [21][22][23]. As a marker for SES, we used educational level and receipt of social support.…”
Section: Discussionsupporting
confidence: 87%
“…Most importantly, their children had higher HbA1c levels. This finding is in keeping with larger studies on disparate outcomes in T1D for pediatric populations, with children in lower income households or with parents of low education levels suffering from a myriad of poor health indicators [22][23][24][25][26]. Thus, the benefit of male partners sharing in night-checks or "helping out" with diabetes care does not necessarily translate to improved HbA1c levels.…”
Section: Discussionsupporting
confidence: 61%
“…Service sector jobs that are commonplace for the working poor rarely allow for paid leave time to accommodate medical visits and render very low wages overall [20,21]. Given tremendous disparities in health outcomes in T1D associated with SES [22][23][24][25][26], it is crucial to examine how features of social context may impact decision-making related to diabetes care, and to identify challenges that may be unique to economically vulnerable families so interventions can be tailored accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates the findings of Berhan et al . , who found that parental SES was associated with mortality in young adults (aged 18–24 years) diagnosed with Type 1 diabetes in childhood in Sweden . While Berhan et al .…”
Section: Discussionmentioning
confidence: 98%